Cognitive and Humanistic Psychology in Islamic Education Learning - Fauziah, Neneng; Muslihah, Eneng; Kultsum, Umi (Maharot : Journal of Islamic Education, 2024)
In studying Islam, cognitive and humanistic plays an important role in internalizing religious values in students and actualizing them in everyday life. This research aims to describe the role of cognitive psychology and humanistic psychology in PAI learning. Researchers in this study used a qualitative approach with a type of library study. The data collection method used is documentation techniques. Next, to analyze the data, descriptive analysis was used. The research results show that cognitive psychology is a learning theory that focuses on the thinking process, where the brain functions in absorbing new knowledge information and carrying out an assimilation process connecting it with initial knowledge to form an understanding. This cognitive theory plays a role in students' activities to understand, digest and assimilate Islamic religious knowledge and store it in memory. Meanwhile, humanistic psychology plays a role in students' efforts to understand their position as servants and their relationship with the Kholik. This research can provide benefits for educators in strengthening students' application of Islamic religious values, so that they can scientifically increase their faith and piety.